Pedestrian–bus route and pickup location planning for emergency evacuation - Lu, Weike; Wang, Feng; Liu, Lan; Hu, Guojing; Mao, Jiannan (Transport, 2021)
Planning for a bus-based regional evacuation is essential for emergency preparedness, especially for hurricane or flood prone urban environments with large numbers of transit-dependent or transit-captive populations. This paper develops an optimization-based decision-support model for pedestrian–bus evacuation planning under bus fleet, pedestrian and bus routes, and network constraints. Aiming to minimize the evacuation duration time, an optimization model is proposed to determine the optimal pickup nodes for evacuees to assemble using existing pedestrian routes, and to allocate available bus fleet via bus routes and urban road network to transport the assembled evacuees between the pickup nodes and designated public shelters. The numerical examples with two scenarios based on the Sioux Falls street network from North Dakota (United States) demonstrates that this model can be used to optimize the evacuation duration time, the location of pickup nodes and bus assignment simultaneously. First published online 13 October 2020